Improvement of PVC compound plasticizer extraction process - Pérez Arteaga, Julia Guadalupe (2022)
The Soxhlet method in extracting plasticizers from PVC compounds presents various areas for improvement, such as the amount of solvent used, the time required in the process, and its costs. This study proposes replacing the Soxhlet method with the ultrasound-assisted method to reduce the time, costs, and amount of solvent used in plasticizer extraction. It also proposes using solvent recovered from previous extractions to reduce costs further. The study involved experimentation with three different grades of PVC compounds (medical, cable, and profile) to compare the recovery of plasticizers by the Soxhlet and the ultrasound-assisted methods. The plasticizers obtained were analyzed using gas chromatography, gas chromatography coupled with mass spectroscopy, and Fourier-transform infrared spectroscopy to evaluate the results of each extraction method as compared to reference compounds and determine any possible interference. The proposed method yields 96 % of plasticizer extraction, a decrease from 360 to 60 minutes in the extraction process, and a decrease from 150 to 100 ml in solvent use. Complemented by the use of recovered solvent, the proposed method reduces costs from 93,000.00 to 15,000.00 Mexican pesos.